Top Three Learning Platforms for Orthopaedic In-Training Knowledge Produce Different Results. (August 2021) - Margalit, Adam; Mixa, Patrick; Day, Louis; Marrache, Majd; Mitchell, Stuart; Suresh, Krishna V.; Wang, Kevin; Sabharwal, Samir; Li, Tuo Peter; Loeb, Alexander; Naziri, Qais; Henn, R. Frank; et al.
Abstract : Objective: To compare the influence of objective and subjective measures of the three learning programs (OrthoBullets [OB], ResStudy [RS], and Clinical Classroom [CC]) on resident test performance and study platform preference. Methods: Sixty residents from three orthopaedic residencies were included in this study during May 2020. Trauma, pediatrics, and hip/knee reconstruction (joints) were chosen as testing topics. Residents took a standardized pretest of 30 questions per topic, followed by the completion of 50 questions per day for 5 days using one of the three web-based programs, followed by a standardized subject-specific posttest. This cycle was repeated for all the three topics. Bivariate statistics and a mixed-effects linear regression model were used to compare improvements in the scores. Results: Across all learning platforms, topics, and postgraduate year classes, posttest scores were 4.4% higher than the pretest score (73.3% vs. 68.9%, P < 0.001): 6.8% higher with OB, 5.4% with RS, and 1.0% with CC. The score improvement with OB was significantly greater than the score improvement with CC ( P < 0.001). In total, 100% of residents reported that using OB would improve their score on the orthopaedic in-training examination, compared with 95% with RS and 67% with CC. Conclusion: OB demonstrated the greatest improvement in scores, followed closely by RS and then CC.